Relationship Between Workload and Nurse Performance in the Inpatient Ward of Nene Mallomo Hospital - Tinta, Yulis; Ekasari, Ekasari; Muhtar, Arlina; Risal, Abd.; Armadi, Armadi (Journal of Community Health Provision, 2024)
Workload is an effort to detail the components and target volume of work in a certain time unit and result unit. Performance is the appearance of the results of personnel's work both in quantity and quality in an organization. The ratio of nursing staff needs is based on the number of patients treated still not meeting the standard. On the one hand, it is said that in providing services to patients, quality must be improved. The type of research used is " Cross sectional" with a point time approach where researchers only take measurements once during the observation. The research location was carried out at the inpatient installation of Nene Mallomo Sidrap Hospital on November 1-30, 2010. The number of samples in this study was 52 people. From the results of the statistical test analysis using Chi square, it was found that there is a relationship between nurses' workload and nurse performance at Nene Mallomo Hospital, Sidenreng Rappang Regency in 2023. The suggestion in this study is expected to regulate nursing staff in terms of quantity and quality so as to reduce the heavy workload which in turn will improve work performance, job satisfaction, and have an impact on improving the quality of nursing care and patient satisfaction.